E Unum Pluribus: After Bond v. United States, State Law as a Gap Filler to Meet The International Obligations of the United States - Llewellyn J. Gibbons (Washington University Journal of Law & Policy, 2015)
Intellectual property issues are among the most significant and hotly contested issues in foreign policy that require treaties that regulate private domestic actors. This Article analyzes two intellectual property examples, one from Berne Convention and the other from the Paris Convention, where state law supplements federal law to provide the minimum level of legal protection required under each treaty. The Article provides an overview of Bond v. United States and then analyzes whether the federal law of preemption or principles of international law require states to develop their law in a manner consistent with US foreign policy. The Article then discusses public policy reasons why a state should develop state law in a manner consistent with the position of the United States in international forums. Finally, this Article concludes that if a judicially created federalism space in foreign relations is constructed in which Congress cannot act to enforce US foreign policy, the de facto motto will change from e pluribus unum (“out of one, many”) to e unum pluribus (“out of one, many), thereby upsetting the obligation and intention of the founding fathers that the United States will speak in foreign lands with one voice.
Keywords: Llewellyn Gibbons; Bond v. United States; Berne Convention; Paris Convention; intellectual property; e pluribus unum; e unum pluribus